P3.041 Identifying and Characterizing Places For the Targeted Control of HIV in Urban Areas. (13th July 2013) - Polk, S; Ellen, J M; Fichtenberg, C; Huettner, S; Reilly, M; Parekh, J; Jennings, J M
Abstract : Background: HIV transmission has been associated with specific populations in specific places, i.e. places where drug and sexual networks overlap consistently. Canvassing places or venues where people congregate has been shown to be an effective means of identifying sexually transmitted infection cases for public health control and surveillance purposes. The objectives of this study were to identify and characterise heterosexual sex partner meeting venues in one U.S. urban area according to according to the presence or absence of HIV cases. Methods: Eighty-seven potential high-HIV-risk heterosexual sex partner meeting venues were identified using a three-phase methodology. Subsequently, a venue-based, cross-sectional study of sexually active 18–35 year olds was conducted in Baltimore, Maryland from October 2008 through December 2009. Results: 1, 594 participants were enrolled at 87 venues. Fifty-nine HIV cases were identified yielding an overall HIV prevalence of 3.7% and a mean venue prevalence of 3.6% (range = 0% to 25%). One or more cases of HIV was identified at 42% (n = 37) of venues (i.e. HIV positive venues). In bivariate analysis, commercial sex work (OR: 1.04; 95% CI: 1.01, 1.08), high HIV-risk sexual partnering (OR: 1.11; 95% CI: 1.03, 1.20), recent parenteral risk behaviour (OR: 1.05; 95% CI: 1.01, 1.10) and drug market activity (OR: 2.67; 95% CI: 1.09, 6.52) were reported significantly more frequently at HIV positive versus HIV negative venues. In final age-adjusted models, HIV positive venues had 10% more high HIV-risk sexual partnering (OR: 1:10; 95% CI: 1.01, 1.19) and more than twice as much drug market activity (OR: 2.59; 95% CI: 1.04, 6.46) compared to HIV negative venues. Sex market activity was not significantly associated with venue HIV status. Conclusions: This study highlights characteristics of venues, such as drug markets, that may be important in identifying places which are more likely to have active HIV transmission.